2011
DOI: 10.1007/s13197-011-0442-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality and storability of chicken nuggets formulated with green banana and soybean hulls flours

Abstract: The present study was envisaged to investigate the effect of green banana (GBF) and soybean hulls flours (SHF) on the physicochemical characteristics, colour, texture and storage stability of chicken meat nuggets. The addition of GBF and SHF in the nugget formulations was effective in sustaining desired cooking yield and emulsion stability besides nutritional benefits. Protein and fat contents were decreased (p>0.05), but fibers and ash contents was increased (p<0.05) amongst treatments. The flour formulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 33 publications
9
35
1
11
Order By: Relevance
“…Mean values with different superscript letters in the same row differ significantly (P <0.05) green banana and soybean hulls flours as well as their combinations significantly decreased the redness value of chicken nuggets (Kumar et al 2011). Products hue value was significantly (P <0.05) affected by salt replacement, however value was improved due to pea hull flour addition.…”
Section: Instrumental Colourmentioning
confidence: 90%
See 3 more Smart Citations
“…Mean values with different superscript letters in the same row differ significantly (P <0.05) green banana and soybean hulls flours as well as their combinations significantly decreased the redness value of chicken nuggets (Kumar et al 2011). Products hue value was significantly (P <0.05) affected by salt replacement, however value was improved due to pea hull flour addition.…”
Section: Instrumental Colourmentioning
confidence: 90%
“…The different components of lipids, including total phospholipids, glycolipids and free fatty acids (FFA) were measured by standard procedures as described by Marinetti (1962), Roughan and Batt (1968) and Koniecko (1979), respectively, whereas total glycerides were indirectly calculated by subtracting all these from total lipid values. Total cholesterol content in the lipid extracts was determined according to procedure described by Sabir et al (2003) using LibermanBurchard reagent.…”
Section: Lipid Profilementioning
confidence: 99%
See 2 more Smart Citations
“…However, there were no significant differences in color characteristics due to the type of soy hull pectin, regardless of the presence/absence of PE. Previously, Kumar et al (2013) reported that the addition of 3-5 % crude soy hull flour increased lightness, but decreased redness, and no significant difference in yellowness of chicken nuggets. Recently, Kim et al (2015) reported that alcohol-washed soy hull pectin and insoluble soy fiber (acid and alkali hydrolyzed) slightly decreased redness and increased yellowness of meat emulsions.…”
Section: Color Characteristics Of Meat Emulsionsmentioning
confidence: 93%